The Hardangervidda wild reindeer herd: a problematic management history - Bjerketvedt, Dag K.; Reimers, Eigil; Parker, Howard; Borgstrøm, Reidar (Rangifer, 2014)
The unique and internationally important wild reindeer Rangifer tarandus herd on the Hardangervidda plateau of southern Norway has shown frequent and extreme fluctuations in harvest numbers for the past 60 years, despite considerable effort to stabilize the herd size at a winter carrying capacity of 9000 – 12 000 animals . In the absence of large mammalian predators, herd size is managed through hunting. Here we attempt to unravel the causes of the management problems related to this population by examining the relative roles of historical, biological and management-related processes. From 1900 - 1950 the population remained mainly low due to a combination of generous harvest quotas, poaching and competition from domestic reindeer. From 1950 - 2012 three extreme harvest peaks of between 4500 - 9500 animals occurred, followed by three equally extreme troughs including two shorter periods of total protection. This extreme harvest fluctuation contrasts with the estimated annual harvest of 2300 - 3000 needed to stabilize the winter herd between 9000 - 12 000 animals. We conclude that this population has been difficult to manage mainly because of 1) a management based on frequently unreliable population data on herd size (especially before 2001), 2) lack of in depth analyses and evaluation of both recruitment and sex and age composition and 3) a low and highly variable harvest success (harvest/quota) due mainly to poor hunter mobility, a disadvantage when reindeer must be harvested from large flocks that constantly move upwind, seeking refuge on small areas with few hunters. More reliable population data to create better harvest models plus increased hunter mobility are necessary to attain a more sustainable herd size, implying an improvement of the current herd survey methodology available to local reindeer boards. Finally, a critical and independent evaluation of the scientific methodology employed to study and manage this herd is needed.